The influence of the perceived psychological safety on the development of core competencies among members of student organizations at the University of the Philippines Tacloban College - Velarde, Sherie Ann M.
This study investigated the relationship between the perceived psychological safety and the development of core competencies among members of student organizations at the University of the Philippines Tacloban. This study has shed light on the crucial role of cultivating psychologically safe spaces to maximize the potential and growth of the members of student organizations, so that they may develop essential qualities and skills to equip them for their future academic and/or professional pursuits. A narrative qualitative design was used for this study, and data were gathered through a semi-structured interview with ten selected members of identified student organizations in the said university. The thematic analysis revealed 4 prominent themes: "Safety in Shared Foundations", "Structured and Unstructured Initiatives Reinforcing Psychological Safety", "Cultivating Competence: Skills Development and Acquisition", and "External Patterning for Performance Enhancement." of psychological safety and how it affects the development of competencies. The findings of this study suggest a significant association between high degrees of perceived psychological safety and opportunities for skill development and acquisition through structured initiatives such as trainings and workshops. Further in this study, inference and implications for organizational practices and recommendations to foster psychological safety to promote the development of competencies are discussed.